COVID-19: global level very high risk pandemic - Mawale, Mahesh B.; Mawale, Anupama M. (International Journal Of Community Medicine And Public Health, 2020)
Rapid worldwide spread of coronavirus disease 2019 (COVID-19) has resulted in a global pandemic. The Middle East respiratory syndrome coronavirus (MERS-CoV) was attracted a great international attention due to multiple healthcare associated outbreaks in 2012. The disease is associated with a high case fatality rate of 34.5%, and there is no recommended therapy for it. The current COVID-19 pneumonia pandemic, caused by the severe acute respiratory syndrome 2 (SARS-CoV-2) viruses, is spreading globally at an accelerated rate. The World Health Organization declared COVID-19, a serious public health emergency, of international concern. The present article represents the epidemiology, transmissibility and treatment thought for COVID-19 disease.